Opening Doors to Using Nonprofit Community-Based Services to Better Cope With Breast Cancer: A Descriptive Interpretive Study of Women’s Experience - Barbara Gentil; Susan Usher; Christine Loignon; Dominique Tremblay (Science of Nursing and Health Practices)
Introduction: Nonprofit community-based organizations (COs) are expected to complement specialized cancer care and help meet the needs of people living with and beyond cancer. However, nonprofit community organization (CO) services are underused by women living with and beyond breast cancer (WLWB-BC).